The mark of the researcher's hand: the imperfections of craft in the process of becoming a qualitative researcher. Issue 5 (November 2021) - Brown, Anna
This article draws on insights from the author's doctoral training and fieldwork in pottery making to extend conversations about the 'craft' of qualitative research. Specifically, the imagery of potter and clay is introduced to explore the unfolding of craft – or the development of well-thought-out research – in the process of becoming a qualitative researcher. A longitudinal account of making research and making pottery zooms in on the deeply personal relationship between the craftsperson and their materials to explore the affective relations that emerge in craftwork. By tilting the emphasis towards the processes that bring things into being, rather than the objects that are produced, craft-in-research is conceptualised as a reciprocal shaping of bodies that unfolds in and through the simultaneous becoming of researcher and research.